2021
DOI: 10.3168/jds.2020-19974
|View full text |Cite
|
Sign up to set email alerts
|

Influence of production, reproduction, morphology, and health traits on true and functional longevity in French Holstein cows

Abstract: In the long term, resilient animals are able to maintain their normal biological processes when confronted with environmental perturbations, reducing their risk of being culled. Therefore, longevity can be proposed as an indicator of long-term resilience. Decisions to remove a given dairy cow from the herd are mainly related to low milk production (i.e., voluntary culling) or to reasons other than production (i.e., involuntary culling). The aptitude of animals to delay any culling is defined as true longevity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
2
18
0
3
Order By: Relevance
“…It seems likely that for animals to thrive in different types of environments they will require different mixes of robustness and resilience. It has been shown that there is significant genetic variation in these traits, even after adjustment for production level (Rostellato et al, 2021), which suggests that selection of the optimal blend of resilience and robustness is feasible.…”
Section: What Is Resilience?mentioning
confidence: 99%
See 3 more Smart Citations
“…It seems likely that for animals to thrive in different types of environments they will require different mixes of robustness and resilience. It has been shown that there is significant genetic variation in these traits, even after adjustment for production level (Rostellato et al, 2021), which suggests that selection of the optimal blend of resilience and robustness is feasible.…”
Section: What Is Resilience?mentioning
confidence: 99%
“…Further, they do not provide any information on the underlying nature of the resilience, which may be important when considering resilience to specific types of environmental disturbances or when addressing the question "can we aim to phenotype animals that are 'generally' resilient to all types of challenges?". Nevertheless, productive lifespan data can be, and has been, used in genetic analyses to identify genotypes that survive longer and are thus a priori more resilient (Rostellato et al, 2021;Tarrés et al, 2006). The challenge lies in adequately accounting for the changing (farm) environments in which this productive life is realized, including aspects of e.g.…”
Section: Long-term Consequences Of Resiliencementioning
confidence: 99%
See 2 more Smart Citations
“…Longevity corresponds to (1) true longevity that includes all culling reasons and (2) functional longevity (all culling reasons, except productivity; Sasaki, 2013). It has recently been proposed that functional longevity may be a good proxy for resilience (Rostellato at al., 2021). There is evidence that functional longevity has a genetic control and can be transmitted to progeny, as heritability estimates were around 0.10 (ranging from 0.1-0.29) in cattle (Sasaki, 2013) and in the range of 0.10 to 0.14 in goats (Castañeda-Bustos et al, 2017;Palhière et al, 2018).…”
Section: Introductionmentioning
confidence: 99%